Information Security Applications 15th International Workshop, WISA 2014, Jeju Island, Korea, August 25-27, 2014. Revised Selected Papers - Rhee, Kyung-Hyune; Yi, Jeong Hyun (Security and Cryptology, 2015)
This book constitutes the thoroughly refereed proceedings of the 15th International Workshop on Information Security Applications, WISA 2014, held on Jeju Island, Korea, in August 2014. The 30 revised full papers presented in this volume were carefully reviewed and selected from 69 submissions. The papers are organized in topical sections such as malware detection; mobile security; vulnerability analysis; applied cryptography; network security; cryptography; hardware security; and critical infrastructure security and policy.